Assessment learning 1 - Boholano, Helen B.; Balo, Vincent Theodore M.; Oliveros, Joey C.; Obaob, Geronimo S. Jr.; Fernandez, Beverly B.; Alejandro, Isidro Max V.; Betarmos, Norla Grace A.; Sabornido, Elna B.; De Rosas, Eva Rivera (Malabon City : Mutya Publishing House, Inc., 2022)
Assessment is an essential part in the teaching and learning process. This is a well-timed manuscript on Assessment in Learning 1. It seeks to present an activity based assessment approach by presenting the latest and practical application in the field to portray it as a significant piece of written work to the teachers. The focus of this book is to introduce the 21st century assessment strategies and skills that are necessary for today's generation, expecting that he/she can teach multicultural and diverse learners.
Chapter 1. Preliminary Concepts and Recent Trends -- Overview 1 -- Lesson 1. Basic Concepts in Assessment 2 -- Lesson 2. Factors Influencing Test Construction and Test Performance 13 -- Chapter 2. Target Setting, Designing and Developing Assessments -- Overview 21 -- Lesson 1. Target Setting 22 -- Lesson 2. Preparation of Classroom Assessment 29 -- Lesson 3. Classroom Assessment Tools 41 -- Lesson 4. Guidelines in Test Construction 47 -- Chapter 3. Qualities of Good Test Instrument -- Overview 67 -- Lesson 1. Assessment Methods 68 -- Lesson 2. Item Analysis 79 -- Chapter 4. Analysis and Interpretation of Assessment Results -- Overview 95 -- Lesson 1. Measure of Central Tendency 96 -- Lesson 2. Measure of Variability 103 -- Chapter 5. Feedbacking and Communicating Assessment Results -- Overview 113 -- Lesson 1. The Normal Curve 114 -- Lesson 2. Functions of Grading and Reporting Systems 123 -- Lesson 3. Parent-Teacher Conference 137 -- Chapter 6. Score Distribution and Measure of Correlation -- Overview 143 -- Lesson 1. Measure of Correlation 144 -- Chapter 7. Computer-Based Assessment -- Overview 159 -- Lesson 1. Introduction to Computer-Based Assessment 160 -- Lesson 2. Creating Assessment using Applications 171.
Includes bibliographical references.
Keywords: EDUCATIONAL TESTS AND MEASUREMENTS